THE USE OF INFORMATION TECHNOLOGY AND COMMUNICATION: WORKFLOW SYSTEM FOR GREATER INTEGRATION OF SUPPLY CHAIN - Viagi, Arcione Ferreira; Panizzolo, Roberto; Alves, João Murta; Crescenzo, Alberto Maria de (Revista Ciências Exatas, 2023)
The global competition has imposed challenges to Supply Chain (SC) integration, mainly, during the process of obtain information to make Demand Management decisions. This paper proposes an integrated model for data collection, analysis, and results dissemination in the SC, contributing to research and alternatives for “The Bullwhip Effect” issue.